Effect of Low Oxygen Concentrations on Trophoblast-Like Cell Line Invasion - Lash, G.E.; Hornbuckle, J.; Brunt, A.; Kirkley, M.; Searle, R.F.; Robson, S.C.; Bulmer, J.N. (Placenta (Eastbourne), 2007)
The applicability of trophoblast-like cell lines to the study of trophoblast function has been widely debated. The present study investigated the effect of oxygen on the invasiveness, apoptosis, proliferation and secreted proteases of four different trophoblast cell lines; HTR-8/SVneo, SGHPL-4, JEG3 and JAR. All experiments were performed at 20% and 3% oxygen for 24, 48 and 72 h. Immunostaining for integrins α1, α6 and β3, cytokeratin 7 and HLA-G was used to determine the phenotype of the different cell lines. Invasion was assessed using the Matrigel invasion assay. Immunostaining for M30 and Ki67 determined levels of apoptosis and proliferation, respectively. Gelatin and casein/plasminogen zymography were performed on conditioned media to determine levels of secreted matrix metalloproteinase (MMP) 2 and MMP9 and urokinase plasminogen activator (uPA), respectively. None of the cell lines immunostained for all markers normally expressed by extravillous trophoblast cells. Invasiveness of HTR-8/SVneo and JEG3 cells cultured in 3% oxygen was increased after 24 h but was inhibited by 72 h in culture. Invasion of SGHPL-4 cells was inhibited after culture in 3% oxygen for 24 h. Invasion by JAR cells was not affected by changes in oxygen concentration. The different cell lines also displayed different responses to culture period in 3% oxygen with respect to apoptosis, proliferation and secreted proteases. Care should be taken before results obtained using cell lines as a model for EVT are extrapolated to extravillous trophoblast cell behaviour in vivo.